2015
DOI: 10.1017/s1743921316002143
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and activity of planet hosting stars

Abstract: Abstract. The magnetic activity levels of planet host stars may differ from that of stars not known to host planets in several ways. Hot Jupiters may induce activity in their hosts through magnetic interactions, or through tidal interactions by affecting their host's rotation or convection. Measurements of photospheric, chromospheric, or coronal activity might then be abnormally high or low compared to control stars that do not host hot Jupiters, or might be modulated at the planet's orbital period. Such detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Alternative activity indicators have been used to search for evidence that tidal interactions stoke stellar activity (see reviews by Wright and Miller 2015;Poppenhaeger 2017). For example, Poppenhaeger and Wolk (2014) and Miller et al (2015) found enhanced stellar coronal Xray emission from host stars that are expected to have strong tidal interactions with their hot Jupiters.…”
Section: The Possible Role Of Stellar Obliquitymentioning
confidence: 99%
“…Alternative activity indicators have been used to search for evidence that tidal interactions stoke stellar activity (see reviews by Wright and Miller 2015;Poppenhaeger 2017). For example, Poppenhaeger and Wolk (2014) and Miller et al (2015) found enhanced stellar coronal Xray emission from host stars that are expected to have strong tidal interactions with their hot Jupiters.…”
Section: The Possible Role Of Stellar Obliquitymentioning
confidence: 99%